2021
DOI: 10.22201/fesz.23958723e.2021.0.293
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de quitosano comercial y extractos acuosos de mesocarpio de coco (Cocos nucifera L.) para el control de Rhizopus stolonifer aislado de guanábana (Annona muricata L.): Pruebas in vitro

Abstract: La eficacia antifúngica de los extractos acuosos de mesocarpio de coco (Cocos nucifera L.) (EAC) y el quitosano comercial (QC) aplicados de manera individual y en combinación se evaluó contra Rhizopus stolonifer en términos de crecimiento micelial, esporulación y germinación de las esporas, así como la obtención de los modelos de crecimiento primario en dos temperaturas de almacenamiento (15-25 ºC). La aplicación de los EAC al 10% redujo significativamente el crecimiento micelial de R. stolonifer (58.81 ± 6.48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The sporulation process of the genus Fusarium plays a key role in the disease cycle through spores, and in this sense, wounds caused by cutting off the hands after harvest are the point of access of spores to the crown; with favorable conditions, the spore can germinate, infect the fruit tissues, and induce necrosis and detachment of the fruit [36,37]. The in vitro results of this research are in agreement with the report by Cortés-Rivera et al [17] against the blue mold agent in citrus and Rhizopus stolonifer, the soft rot agent in soursop [38]. The differences in the efficacy of treatments depending on the fruit tissue could be related not only to the nutrient composition of tissues [39] but also to the affectation of fungus due to the extract exposition in tissues, playing a key role in the fungus development as evidenced by SEM (Figure 7b,d).…”
Section: Discussionsupporting
confidence: 89%
“…The sporulation process of the genus Fusarium plays a key role in the disease cycle through spores, and in this sense, wounds caused by cutting off the hands after harvest are the point of access of spores to the crown; with favorable conditions, the spore can germinate, infect the fruit tissues, and induce necrosis and detachment of the fruit [36,37]. The in vitro results of this research are in agreement with the report by Cortés-Rivera et al [17] against the blue mold agent in citrus and Rhizopus stolonifer, the soft rot agent in soursop [38]. The differences in the efficacy of treatments depending on the fruit tissue could be related not only to the nutrient composition of tissues [39] but also to the affectation of fungus due to the extract exposition in tissues, playing a key role in the fungus development as evidenced by SEM (Figure 7b,d).…”
Section: Discussionsupporting
confidence: 89%
“…28,35,46 In addition, chitosan is a bio-stimulant of growth-promoting microorganisms of the type: Trichoderma spp., 29 such as genera and species of mycorrhizal fungi 47 of actinomycetes: Streptomyces, Kitasatospora, since they synthesize chitosanases that hydrolyze chitosan to use it as a carbon and nitrogen source. 48 While chitosan is compatible with other plant products such as botanical extracts 12 and carbon nanoparticles, 49 with antagonistic activity.…”
Section: Application Of Chitosan In Agriculturementioning
confidence: 99%
“…28 It is reported that chitosan interferes with the transformation of DNA into RNA, prevents cell growth, as well as the synthesis of proteins linked to carbohydrates, affects the genetic regulation of chitin synthesis in the cell wall. 28,52,60 In the microbial spores, it causes disorganization of the cytoplasm with loss of intracellular content, affects the spore membrane, 52 due to the relationship of the amino groups of chitosan that interact with the negative charge of the cell membrane of the spore and inhibits germination 12 In the mycelium, the loss of nutrients causes vacuolation, with the formation of thin, distorted, and malformed hyphae. 53 In the genera and species of Gram negative (-) bacteria, chitosan is attracted by electrostatic attractions, with lipopolysaccharides of the outer membrane, and affects permeability.…”
Section: Control Of Phytopathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan was extracted from different fungal species such as, Cunninghamella elegans (0.75 g l -1 ), C. blakesleeana (9.4 % of fungal biomass), Rhizomucor miehei (13.67 %), Mucor rouxii (1.2 %) Cladosporium Cladosporioides (25.2 mg/g) with degree of deacetylation 81 %, 35 %, 80.6 % and 59 %, respectively (George et al, 2011;Miyoshi et al, 1992;Tajdini et al, 2010;Tayel et al, 2016). As well as the extracted chitosan of some fungi was tested for their biotechnological applications in water pollutant elimination (heavy metals and waterborne microorganisms) and removal of toxic pollutants biocontrol of postharvest diseases (Betchem, et al, 2019;Cortés-Rivera et al, 2021) ). Furthermore, these results provide a promising approach for concomitant production of paclitaxel and chitosan sources and increase the possibility for production and extraction of fungal chitosan with well-defined properties at an industrial scale.…”
Section: Chitosan Production From Fungal Biomass Residuementioning
confidence: 99%